IMPLEMENTASI KEBIJAKAN TENTANG STANDAR PELAYANAN MINIMAL JALAN TOL MENURUT PERATURAN MENTERI PEKERJAAN UMUM NOMOR 392/PRT/M TAHUN 2005 DI KOTA SEMARANG - Fajrin, Nurul; Kismartini, Kismartini; Rengga, Aloysius (Journal of Public Policy and Management Review, 2015)
Indonesian Government Regulation No. 15 Year 2005 on the highway there is a setting highways, highway conditions, the implementation of the toll road authority, setting highways, highway construction, toll road, highway monitoring, land acquisition, and minimum service standards highway. In the minimum service standards according to the highway Minister of Public Works No. 2005 includes some substance 392/PRT/M ministry that highway conditions, the average travel speed, accessibility, mobility, safety, and rescue units / rescue and relief services. This study aims to determine how the implementation of minimum service standards policy in Semarang toll road by the Minister of Public Works No. 392/PRT/M 2005 and what factors are affecting the implementation of the policy. The method used in this research is descriptive qualitative research type with in-depth interviews to the informant. In qualitative research, the authors determined the informant using the snowball technique (snowball). The data source using the primary data source and secondary data source. Collecting data with interview techniques, and documentation. Data analysis techniques using data reduction (data reduction), presenting data (data display), and verification (conclution drawing). Based on these results, it can be concluded as follows: First, implementing policies that the accuracy of existing programs currently running less effective, this policy instrument of policy and lack of socialization SPM highways to toll road users, the current policy actors less responsive in addressing barriers and traffic, and not all highway users do not get the benefits of those policies. Second, the factors that affect the implementation of policies that communication can not be run effectively, resources has yet to realize the programs that will be developed, and the disposition / attitude highways officers less assertive in action against toll road users who break the rules. The authors suggestion to this problem is to Semarang toll road management should provide clarity about the programs that will be implemented to improve the quality of service that the public toll road toll road users can experience the benefits of the program to be developed. Besides highways officers should be more responsive in handling traffic constraints and barriers that occur. On the other hand the toll road users should be able to obey traffic rules and especially against traffic signs about the do's and don'ts as well as the instructions.